Upgrading Rural Youths’ Capacity for Driving Shrimp-Based Agribusiness Value Chain in Nigeria - Odemero , Achoja Felix; Miebi , Gbigbi Theophilus; Aramide, Ikpoza Eguono; Ebidenere , Denghan Janet (Asian Journal of Agriculture and Rural Development, 2020)
This study derives its significance from the current debate on ageing agricultural labour force in Nigeria and the need for capacity building of rural youth. This study investigates rural youth capacity for driving shrimp-based agribusiness development in Nigeria. Data for the study were obtained from primary sources using a structured questionnaire with randomly selected 120 shrimp operators (harvesters, processors and marketers). Statistical analytical tools (descriptive and inferential statistics) were employed to analyze the collected data. Test of the hypothesis implies that the mean income earned by youth is significantly (p < 0.01) higher that the income of aged workforce in the shrimp agribusiness value chain. Further finding shows that human capital of youth (shrimp-oriented education, training, workshops attended and access to credit) has a positive and significant (p < 0.01) effect on their financial performance. Incentives such as loans and aquaculture-oriented education and regular workshops should be given to the rural youth to upgrade their capacity to drive the development of shrimp-based agribusiness in Nigeria in the future.